Factors affecting the acceptability of isoniazid preventive therapy among healthcare providers in selected HIV clinics in Nairobi County, Kenya: a qualitative study. Issue 12 (19th December 2018) - Wambiya, Elvis Omondi Achach; Atela, Martin; Eboreime, Ejemai; Ibisomi, Latifat
Abstract : Objective: Despite being globally recommended as an effective intervention in tuberculosis (TB) prevention among people living with HIV, isoniazid preventive therapy (IPT) implementation remains suboptimal, especially in sub-Saharan Africa. This study explored the factors influencing the acceptability of IPT among healthcare providers in selected HIV clinics in Nairobi County, Kenya, a high HIV/TB burden country. Design: A qualitative study was conducted using in-depth interviews with healthcare providers in selected HIV clinics. All conversations were audio recorded, transcribed verbatim and analysed using a thematic approach. Setting: The study was conducted in the HIV clinics of three purposefully selected public healthcare facilities in Nairobi County, Kenya between February 2017 and April 2017. Participants: Eighteen purposefully selected healthcare providers (clinicians, nurses, pharmacists and counsellors) working in the HIV clinics participated in the study. Results: Provider acceptability of IPT was influenced by factors relating to the organisational context, provider training on IPT and their perception on its efficacy, length and clarity of IPT guidelines and standard operation procedures, as well as structural factors (policy, physical and work environment). Inadequate high-level commitment and support for the IPT programme by programme managers and policy-makers were found to be the major barriers to successful IPT implementation in our study context. Conclusion: This study provides insight into the complexity of factors affecting the IPT implementation in Kenya. Ensuring optimal acceptability of IPT among healthcare providers will require an expanded depth of engagement by policy-makers and IPT programme managers with both providers and patients, as well as on-the-job design specific actions to support providers in implementation. Such high-level commitment and support are consequently essential for quality delivery of the intervention.